2014
DOI: 10.1111/jicd.12133
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of a herbal and a non‐herbal dentifrice on dentinal hypersensitivity: a randomized, controlled clinical trial

Abstract: The herbal dentifrice showed comparable results to the non-herbal dentifrice and can be recommended for the treatment of DH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Interestingly, some studies reported significant DH reduction in groups absent from active principle, indicating the possible contribution of the placebo effect or even the Hawthorne effect on the action of desensitisers . In the case of the placebo effect, the participants would present a physiological response after administration of an inert agent, such as saline solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, some studies reported significant DH reduction in groups absent from active principle, indicating the possible contribution of the placebo effect or even the Hawthorne effect on the action of desensitisers . In the case of the placebo effect, the participants would present a physiological response after administration of an inert agent, such as saline solution.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, three studies were included that refer to a statistical improvement in DH with the use of herbal dentifrices, two of which refer to the agent Spinacia oleracea. 79,92,93 However, the presence of potassium nitrate in the composition of the described dentifrices does not allow a correct understanding of the true nature of the desensitising effect of Spinacia oleracia in the treatment of DH, since this effect may be due to the nitrate in the composition of the product.…”
Section: Percentage Of Dh Reduction Between Baseline and Final Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many toothpastes with the various herbal structures are developed, and their capability in the tubule occlusion are reported (Kaur, Paul, Rathee, & Arora, 2020;Kumari, Naik, Martande, Pradeep, & Singh, 2016;Vajrabhaya, Korsuwannawong, Harnirattisai, & Teinchai, 2016). Moreover, in an in vitro study, the effectiveness of the toothpastes having silica as abrasives in tubular occlusion process was analyzed (Addy & Mostafa, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…TG 3 group showed effective results but slowly that can be observed from Tables 1–5. Kumari et al 2016[31] compared the efficacy of herbal and nonherbal dentifrices against DH on 145 patients having DH and were randomly divided into three groups: placebo, herbal, and nonherbal groups. The result showed herbal dentifrices was more effective than the nonherbal group.…”
Section: Discussionmentioning
confidence: 99%